Do family-owned banks perform better? A study of Malaysian banking industry - Ong, Tze San; Gan, Shih Sze (Canadian Center of Science and Education, 2013)
It has been discussed that whether family ownership perform better or less perform than non-family ownership that might create or destroy agency costs among the managers and shareholders. This paper is to investigate the financial performance of family and non-family owned banks in Malaysia from year 2001 to 2010. This study compares the financial performance of family and non-family owned banks that operate under central bank of Malaysia, (BNM) and are listed on Bursa Malaysia. Multiple regression technique was performed to investigate the relationship between independent variable (ownership structure) and dependent variables (Tobin’s Q, ROA and ROE). Findings indicate that Tobin’s Q is the best fit as the dependent variable for the regression model. It shows the highest F statistics value, which is 6.247 as compared to ROA and ROE for full sample. Meanwhile, the adjusted R squared of Tobin’s Q indicates similar higher value as well that is 0.150 between the dependent variables. Board composition and board size indicate strong influence on the performance of family-owned banks. Smaller board size on the board can help the bank to achieve better performance in term of Tobin’s Q and ROE. In contrast, board composition attains better performance in term of ROA rather than Tobin’s Q and ROE. This study can provide useful insights of the governance mechanism that could influence the firm performance.